U.S. Beef Demand Drivers and Enhancement Opportunities - Tonsor, Glynn T.; Mintert, James; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This publication uses national, quarterly data to examine U.S. meat demand using the Rotterdam model. The analysis provides insights into beef demand and previously unexamined topics including the effect of multiple information indices linking different health concerns with diet, changes in household dynamics, and meat recall information. Estimation results confirmed that consumer expenditures are a very important beef demand determinant, which means that beef demand is sensitive to the strength of the U.S. economy. Results also indicate consumers respond to the receipt of information about beef and nutrition. For example, publication of medical journal articles linking iron, zinc, and protein with health and diet increase beef demand whereas publication of articles dealing with fat, cholesterol, and diet concerns reduce beef demand. Overall, model results also suggest that beef demand suffered, and poultry demand benefitted, as U.S. consumers’ demand for more convenient meat products increased. In particular, as U.S. consumers consumption of food away from home increased, beef demand declined. Consumers are also sensitive to food safety. When USDA Food Safety Inspection Service beef product recalls increase, beef demand declines. Moreover, beef product recalls have a significant positive spillover effect on poultry demand, suggesting that consumers shift away from beef and toward poultry products in response to beef food safety recalls. In summary, this research provides a more complete understanding of the influence multiple information factors have on consumer demand for beef. Future research could explore the use of additional media indices focusing on animal welfare, environmental concerns, and other aspects of human health to estimate their impact on beef demand. Additionally, future research should also consider the use of scanner data to obtain better measures of prices paid by consumers for meat products and to more narrowly identify some of the specific determinants of the findings from this study.
Keywords: Beef; Diet; Consumer demand; Health